USING E-LEARNING TO SUPPORT LEARNING AND TEACHING LANGUAGE: The Importance of Virtual Learning Environments (VlE) to Improve Students` Sepaking Ability - Anita Anggraeni (Eltin Journal : Journal of English Language Teaching in Indonesia, 2014)
It is not enough to train and empower  students through out-dated and traditional methods of learning. Technology has the power to transform education. It is essential to bring it into the classroom to empower learning. Besides the extensive impact on communication and business, the Internet is poised to cause a paradigm shift in the way people learn. Nowadays anywhere, anytime, education is possible. Recently speaking has played an increasingly important role in second/foreign language settings.  However, in many universities in Indonesia, EFL students rarely communicate in English effectively. This present study aims at investigating the implementation of Virtual Learning Environments (VLE) and its effect on EFL learners` speaking in one college in the southern of Bandung.  This college already makes Memorandum of Understanding with one of prestigious college in Malaysia.  One of the programs is making a long distance lecturing using VLE e-learning. Speaking pretest and post test, student interaction in VLE e-learning recording analysis, student questionnaires, and student interviews constitute  data collection during the 4-week instruction period.  Results show that VLE e-learning have positive effects on improving students` speaking in terms of language quality and the improvement of vocabulary, and students express opinions on the implementation of VLE e-learning. Keywords:   VLE e-learning, technology, education